Vocational High School Culture - Rifma Rifma; Rusdinal Rusdinal; Ranti Meizatri (RedWhite Press, 2018)
School culture becomes one of the determinants formed of students work culture. The lack of attention of school culture has an adverse effect on the character building of students to the low productivity and effectiveness of the school. The aim of the research was to obtain data and information about school culture development in vocational high school. The research employed qualitative research. This research was done in Vocational High School (SMK) Negeri 9 Padang which is one of the favorite vocational high school with all accredited skills program A. Subjects in this research were principal, head majors, teachers, employees, and pupils. Data in this research was collected by using observation, interview, and documentation study. Data were analyzed through three stages: data reduction, data presentation, and conclusion. The results of this study describe the culture of SMK Negeri 9 Padang seen from: (1) behavior; (2) norms; (3) dominant values; (4) philosophy; (5) rules; (6) school climate. The culture has been developing are hospitality culture and work above standard.